Clinical characteristics of 683 children and adolescents, aged 0-18 years, newly diagnosed with type 1 diabetes mellitus in Henan Province: a single-center study - Ai Huang; Qiong Chen; Wei Yang; Yan Cui; Qingzhi Wang; Haiyan Wei (BMC, 2023)
Abstract Background Type 1 diabetes mellitus (T1DM) is a common chronic systemic disease that threatens the health of children worldwide. Diabetic ketoacidosis (DKA) is the most severe acute complication of diabetes and can lead to death. This study aimed to explore the epidemiological features, clinical manifestations, and risk factors for DKA in children and adolescents newly diagnosed with T1DM in the Department of Endocrinology of the Children's Hospital of Henan Province. Methods Medical records of 683 children and adolescents newly diagnosed with T1DM in our center from March 2014 to November 2021 were retrospectively analyzed. The data included the general condition, laboratory indexes, and clinical symptoms. The patients were divided into three groups according to age: Group I, 0-3 years; Group II, 4-9 years; and Group III, 10-18 years. Results The incidence of DKA was 62.96% and was highest in Group I. Group I had the lowest C-peptide and hemoglobin A1c, but the highest blood glucose at first diagnosis, and 25-hydroxyvitamin D3 levels, hospitalization lengths, and medical costs. 25.5% of the children were delayed in diagnosis. Logistic regression analysis showed that elevated HbA1c levels and hyperglycemia were independent risk factors for DKA. On the other hand, C-peptide and 25- hydroxyvitamin D were protective factors for DKA. Conclusions The incidence of DKA among children and adolescents in the Henan Province is very high. Moreover, DKA can be easily delayed in diagnosis. Newly diagnosed infants with T1DM are more likely to present with DKA, suffer more severe metabolic disorders, endure longer hospital stays, and accrue higher medical costs.